Currículo escrito e a história da Educação Física no Brasil (1896-1945) - Silva, Ribamar Nogueira da (Universidade Federal de São Carlos, 2016)
This study, conducted from bibliographical research with primary sources, deals with the relationship between curriculum and history of Physical Education in Brazil, in First Brazilian Republic (1889-1930) and Vargas Era (1930-1945) periods. Initially, it presents an analysis of the Comenius' Didactica Magna, Society of Jesus' Ratio Studiorum and Brothers of Christian Schools' Conduite des écoles chrétiennes, as historical landmarks of modern curriculum. Then it brings the debate about the Traditional, Critical and Post-Critical theories of curriculum, in particular, the brazilian's Physical Education curriculum. Further, based on authors of the curriculum field of study and using an historical perspective, it delimits the concept of written curriculum. Using that concept, it identified written curriculum manifestations in the concrete reality of Brazilian education. As it approaches the relationships involved in the historical production of the curriculum, it defines two temporal cut. The first, from Arthur Higgins' Compendio de gymnastica e jogos escolares publish (1896) to 1929, date in which the so-called French method was introduced in civil Physical Education, becoming mandatory in all educational institutions in Brazil. The second, Regulamento (N° 7) da Educação Física (Método Francês) publish (1932) until the year 1945, characterized by weakening of French doctrine and military ideas, which mark the end of the Vargas Era. Finally, it concludes that Higgins' Compendio is a watershed in the history of Brazilian Physical Education curriculum, because it has the kind of modern curriculum development, based in Traditional Curriculum features in development in the first decades of the twentieth century. This study also affirms that the Regulamento (No. 7) was produced in complementary relationship to the Revista da Educação Física, a fact that reveals one of the ways in which the curriculum of the Brazilian Physical Education developed in that historical period.
Written curriculum and the history of physical education in Brazil (1896-1945)
Keywords: Educação física - Currículos; Physical education and training; História da educação; Education - History; Currículos; Education - Curricula; CIENCIAS HUMANAS::EDUCACAO::CURRICULO